2021
DOI: 10.1681/asn.2021040548
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Renal Outcomes, Kidney Failure, and Mortality in Obese Kidney Donors

Abstract: BackgroundObesity is associated with the two archetypal kidney disease risk factors: hypertension and diabetes. Concerns that the effects of diabetes and hypertension in obese kidney donors might be magnified in their remaining kidney have led to the exclusion of many obese candidates from kidney donation.MethodsWe compared mortality, diabetes, hypertension, proteinuria, reduced eGFR and its trajectory, and the development of kidney failure in 8583 kidney donors, according to body mass index (BMI). The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Multiple studies in LKDs [43][44][45] report mortality risk as similar to matched healthy nondonors, but these studies were not risk-stratified by BMI. Ibrahim et al 46 reported comparable mortality risk with nonobese donors. In a study of 119,769 living donors in the United States, the cumulative incidence of long-term mortality at 20 years postdonation for obese donors was 304.3 per 10,000 donors compared to 208.9 per 10,000 among nonobese donors.…”
Section: Medical Riskmentioning
confidence: 90%
See 3 more Smart Citations
“…Multiple studies in LKDs [43][44][45] report mortality risk as similar to matched healthy nondonors, but these studies were not risk-stratified by BMI. Ibrahim et al 46 reported comparable mortality risk with nonobese donors. In a study of 119,769 living donors in the United States, the cumulative incidence of long-term mortality at 20 years postdonation for obese donors was 304.3 per 10,000 donors compared to 208.9 per 10,000 among nonobese donors.…”
Section: Medical Riskmentioning
confidence: 90%
“…There is a higher incidence of proteinuria in obese LKDs compared to nonobese LKDs, reported in different studies to range between 17.8% to 44% versus 13-17%. 46,50,51 Studies with short-term follow up of obese donors reported no differences in GFR compared to nonobese donors. 40,52,53 Two single-center studies reported no significant differences in eGFR of obese LKDs compared to nonobese LKDs, and the risk of ESRD was 0.7% in obese versus nonobese LKDs.…”
Section: Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…While LKDs with obesity have become more prevalent-nearly 25% of LKDs nationally have obesity, the long-term safety of donation in this population is unknown [14][15][16]. Our understanding of the impact of kidney donation on lifetime ESKD development-the guiding principle of donor selection-remains limited as most studies report mean follow-up of 20 years or less [17][18][19]. Given the concern for kidney disease development or progression in the setting of diabetes and uninephrectomy [20][21][22], the need to evaluate intermediate outcomes of ESKD, such as diabetes development among LKDs with obesity, is critical to guide donation practices and prioritize LKD safety.…”
Section: Introductionmentioning
confidence: 99%